2012
DOI: 10.1021/jp300934h
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Catalytic Effects of Graphene Nanofibers on Hydrogen Release of Sodium alanate

Abstract: One of the most technically challenging barriers to the widespread commercialization of hydrogen-fueled devices and vehicles remains hydrogen storage. More environmentally friendly and effective nonmetal catalysts are required to improve hydrogen sorption. In this paper, through a combination of experiment and theory, we evaluate and explore the catalytic effects of layered graphene nanofibers toward hydrogen release of light metal hydrides such as sodium alanate. Graphene nanofibers, especially the helical ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 31 publications
1
13
0
2
Order By: Relevance
“…Similarly, a combination of experimental and theoretical calculations has been used to rationalize the catalytic activity of G nanofibers for hydrogen release from sodium alanate (NaAlH 4 ). 80 It was found that G nanofibers considerably improve hydrogen release from NaAlH 4 , which is of significance for the implementation of NaAlH 4 for environmentally friendly and effective hydrogen storage and release. DFT revealed that carbon atoms at sheet edges, regardless whether zigzag or armchair, can weaken Al-H bonds in sodium alanate.…”
Section: Edgesmentioning
confidence: 95%
“…Similarly, a combination of experimental and theoretical calculations has been used to rationalize the catalytic activity of G nanofibers for hydrogen release from sodium alanate (NaAlH 4 ). 80 It was found that G nanofibers considerably improve hydrogen release from NaAlH 4 , which is of significance for the implementation of NaAlH 4 for environmentally friendly and effective hydrogen storage and release. DFT revealed that carbon atoms at sheet edges, regardless whether zigzag or armchair, can weaken Al-H bonds in sodium alanate.…”
Section: Edgesmentioning
confidence: 95%
“…Каталітичну активність ВОГ у реакціях гідрування було показано на прикладі відновлення нітросполук до амінів за допомогою NaBH 4 , гідразингідрату та NaAlH 4 [6][7][8]. Також було виявлено, що ВОГ є каталітично активним у гідруванні органічних сполук молекулярним воднем у рідкій фазі за високого тиску [9,10].…”
Section: каталітичні властивості нановуглецевих матеріалів у реакції селективного гідрування ацетиленуunclassified
“…The main difference between these types of catalyst is the availability of active sites, which is responsible for the catalytic behavior. The fundamentals behind the catalytic activities of CNFs have also been investigated by the model interaction of NaAlH 4 with various edge sites of one single-layer graphene from fi rst principal theory, and the details of theoretical modeling results have been described by Qian et al [109]. Both zigzag edge and armchair edge are considered for the study (shown in Figure 4.11[a-f]).…”
Section: Longer Bondsmentioning
confidence: 99%